Impact of the Addition of Examples to the American Society of Anesthesiologists Physical Status Classification System. (March 2020) - Fielding-Singh, Vikram; Willingham, Mark D.; Grogan, Tristan; Neelankavil, Jacques P.
Abstract : Examples of comorbidities for the widely used American Society of Anesthesiologists physical status (ASA-PS) classification system were developed and approved in 2014. We conducted a retrospective cohort study of patients with 4 comorbidities included in the examples as warranting a specific minimum ASA-PS class. For each comorbidity subgroup, we used interrupted time-series models to compare ASA-PS underclassification for the periods before (2011–2014) and after (2015–2017) the introduction of examples. Rates of underclassification ranged from 4.8% to 38.7%. We observed no evidence of a significant impact on ASA-PS classification with the introduction of examples in 2014.